2010
DOI: 10.1021/jm100962a
|View full text |Cite
|
Sign up to set email alerts
|

Acetic Acid Derivatives of 3,4-Dihydro-2H-1,2,4-benzothiadiazine 1,1-Dioxide as a Novel Class of Potent Aldose Reductase Inhibitors

Abstract: A series of novel benzothiadiazine 1,1-dioxide derivatives were synthesized and tested for their inhibitory activity against aldose reductase. Of these derivatives, 17 compounds, having a substituted N2-benzyl group and a N4-acetic acid group on the benzothiadiazine, were found to be potent and selective aldose reductase inhibitors in vitro with IC50 values ranging from 0.032 to 0.975 μM. 9m proved to be the most active in vitro. The eight top-scoring compounds coming from the in vitro test for ALR2 inhibition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 51 publications
2
39
1
Order By: Relevance
“…(Figure 1). [2] Nowadays, in order to satisfy the need of a daily expanding global market, synthesis of new 1,2-benzothiazinane compounds is in high demanded. [2] Nowadays, in order to satisfy the need of a daily expanding global market, synthesis of new 1,2-benzothiazinane compounds is in high demanded.…”
mentioning
confidence: 99%
“…(Figure 1). [2] Nowadays, in order to satisfy the need of a daily expanding global market, synthesis of new 1,2-benzothiazinane compounds is in high demanded. [2] Nowadays, in order to satisfy the need of a daily expanding global market, synthesis of new 1,2-benzothiazinane compounds is in high demanded.…”
mentioning
confidence: 99%
“…In literature, there are many studies on the inhibition of AR. For example, Chen et al studied acetic acid derivatives of 3,4‐dihydro‐2 H ‐1,2,4‐benzothiadiazine‐1,1‐dioxide inhibiting AR and they determined that their compound 8a showed most selective and potent inhibition. In another study, novel benzofuroxane derivatives showed AR inhibitory and compounds 46a , b in that study displayed promising profiles as ARI among them …”
Section: Resultsmentioning
confidence: 99%
“…Ponalrestat was withdrawn from clinical trials due to lack of efficacy. Besides, a number of potent ARIs were recently designed and synthesized based on various chemical core structures including (benzothiazol-2-yl)methylindole (lidorestat) [36], naphtho [1,2-d]isothiazole [55], oxadiazole [56], aromatic thiadiazine-1,1-dioxide [57,58], and quinoxalinone [59]. All of them bear a chemical group of acetic acid on the core.…”
Section: Ar Inhibitorsmentioning
confidence: 99%